1987
DOI: 10.1016/s0735-1097(87)80241-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of intravenous digoxin in patients with severe heart failure initially treated with diuretics and vasodilators

Abstract: The purpose of this study was to assess the hemodynamic effects of intravenous digoxin in patients with New York Heart Association class IV heart failure, who had never previously been treated with digitalis drugs, and who were initially treated only with diuretics and systemic vasodilators to clinical end points of compensation. Eleven male patients, 5 with idiopathic and 6 with ischemic cardiomyopathy, had sinus rhythm and were hospitalized with congestive heart failure not precipitated by an acute ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…86 for review). Clinically, it is important to note that the hemodynamic benefits of glycosides have been reported to be directly related to the severity of CHF (42), underscoring the importance of altered NKA expression, pump reserve, and the sensitivity to glycoside effects in CHF.…”
Section: Alterations In ␣-Isoform Expression In Diseasementioning
confidence: 99%
“…86 for review). Clinically, it is important to note that the hemodynamic benefits of glycosides have been reported to be directly related to the severity of CHF (42), underscoring the importance of altered NKA expression, pump reserve, and the sensitivity to glycoside effects in CHF.…”
Section: Alterations In ␣-Isoform Expression In Diseasementioning
confidence: 99%
“…Ribner et al [ 17] showed no change in systemic vascular resistance and only a modest reduc tion of pulmonary wedge pressure in re sponse to intravenous digoxin. Gheorghiade et al [18] showed no change in systemic vas cular resistance in patients with clinically compensated failure. On the other hand, in patients with severe heart failure and high wedge pressure (35 ± 8 mm Hg), Gheorgh iade et al [19] showed a significant reduction of pulmonary wedge pressure and systemic vascular resistance in response to intrave nous digoxin.…”
Section: Effects O/digoxinmentioning
confidence: 96%
“…Digitalis glycosides improve myocardial contraction [8]; however, the increase in ino tropic state does not always translate into improved cardiac performance as expressed by cardiac output and left-ventricular filling pressure [2], In patients with congestive heart failure, intravenous digoxin produces a mod est decline in heart rate, a variable increase of mean arterial blood pressure, a modest increase of cardiac output, and an increase of left-ventricular ejection fraction [17,18]. The changes of pulmonary wedge pressure and systemic vascular resistance in response to intravenous digoxin vary considerably.…”
Section: Effects O/digoxinmentioning
confidence: 99%
“…In HF, however, when hemodynamics are normalized first with diuretics and vasodilators, no further improvement in pulmonary capillary wedge pressure or cardiac output is achieved after the acute administration of digoxin. 6,7 The improvement in hemodynamics is sustained during chronic therapy. 8 …”
Section: Hemodynamic Effectsmentioning
confidence: 99%